Prognostic factors affecting survival in stage 3 colorectal cancers (Annals of Medical Research, 2021)
None
Keywords: key. In this study, we consider the clinical and pathologic factors that affect survival in stage 3 colorectal cancer.br /Material and Methods: We analyzed patients who underwent radical surgery for stage 3 colorectal cancer between January 2012 and March 2018 at the Ortadogu Hospital, Adana, Turkey. The age and gender of the patients, the length of the colectomy specimen, the location and size of the tumors, TNM stage and the number of retrieved lymph nodes were evaluated. The lymphovascular and perineural invasion was examined.br /Results: In the group, 73 were men and 52 were women, ranging in age from 22 to 88 years (mean age, 58 years). There were 29 cases of right colon cancer, 30 cases of left colon cancer and 66 cases of rectal cancer. Lymphovascular and perineural invasion were present in 78 patients (62.4%) and 30 patients (24.0%) respectively. Twenty-one patients received preoperative adjuvant therapy. No significant difference was found between tumor size and invasion and mortality. However, we found a statistically significant difference between age, metastatic lymph node, total lymph node number, and mortality. According to the Log-Rank test, we found that lymphovascular and perineural invasion were significant for survival.br /Conclusions: The number of metastatic lymph nodes had a poor prognosis on the survival, we found that the high total number of retrieved lymph nodes affected prognosis in a good way. We conducted that perineural and lymphovascular invasion is a factor affecting the survival adversely in stage 3 colorectal cancers.br / Retrieval Of Pericolorectal Lymph Nodes; Stage 3 Colorectal Carcinoma; T-Classification; N-Classification, Neoadjuvant Therapy; Understaging.